2007
DOI: 10.1097/opx.0b013e318157a6b1
|View full text |Cite
|
Sign up to set email alerts
|

Depression in Older People: Visual Impairment and Subjective Ratings of Health

Abstract: Depression was common in this population of older adults with severe visual impairment. Impaired visual and physical functions were associated with symptoms of depression. The effect of visual disability was independent of the effect of physical disability. The strength of this relationship, and the results of the regression analyses, indicate that a person who is visually or physically disabled is more likely to suffer from depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
132
5
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(150 citation statements)
references
References 36 publications
10
132
5
3
Order By: Relevance
“…Hayman et al found that subjective perceptions of health were more important in explaining feelings of depression than the actual objective measures of visual function [10]. This article supports that finding, because reported depressive levels were independent of actual visual acuity measurements.…”
Section: Relationship Between Depression and Reading ο€  Outcome Measuressupporting
confidence: 70%
See 2 more Smart Citations
“…Hayman et al found that subjective perceptions of health were more important in explaining feelings of depression than the actual objective measures of visual function [10]. This article supports that finding, because reported depressive levels were independent of actual visual acuity measurements.…”
Section: Relationship Between Depression and Reading ο€  Outcome Measuressupporting
confidence: 70%
“…The association between depression and visual impairment has been well documented [3][4][5][6][7][8][9][10]. In a recent study, Hayman et al used depression inventories to determine that older adults with visual impairment report higher levels of depressive symptomatology than older adults without visual impairment [10].…”
Section: Depression and Vision Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies showed that during the developmental stage of children and adolescents with visual impairment, they continue becoming more vulnerable to life circumstances [9]. Low vision is associated with negative consequences such as limitations in day-to-day activities [10,11], poor physical function [10], depressive symptoms [12][13][14][15][16], and low quality of life [17]. There is an internal relationship between sensory impairment, mental and social functioning, and communication [18].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [11][12][13][14][15][16] have stated high rates of depression in people with impaired vision. But only a few researches conducted on visually impaired people have accredited the role of psychological interventions in reducing depression in this group.…”
Section: Introductionmentioning
confidence: 99%